Beyond the Box: Diversity, mediation and new models of demographic data profiling. Issue 2 (17th November 2016) - Shimada, Lia; Stephens, Christopher
Abstract : This research study explores the value of a new methodological approach in data collection for understanding the diverse identities of mediators who constitute the College of Mediators – a national mediation professional body, with members drawn from across the UK. It forms part of a broader project to provide a much-needed critique of the standard 'tick-box' approach to demographic monitoring used by most organisations. Questions were designed to elicit open responses to a range of diversity strands, including age, gender identity, ethnic identity, national identity, religious or spiritual orientation, and sexual orientation. The responses gave useful insights into the ways in which mediators identify as diverse individuals, and the language they use to describe themselves. A picture emerges from this study of an organisation with a strong demographic profile. Yet within this profile, the differences expressed and the language used provide a rich source of data for investigating 'diversity'. The responses to this study affirm the need for a new approach to the collection of demographic data. The paper concludes by drawing out themes which emerge around personal identity and the need for nuanced understanding of human experience. We offer reflections on the data which pose important questions for organisations – such as the College of Mediators – to consider about the relationship between diversity and organisational culture, and we argue for more nuanced understandings of and challenges to the concept of neutrality in mediation.